Compartilhamento do conhecimento nos grupos de processos de gestão de projetos : conteúdo, atores e tecnologia da informação - Gomes, Fernanda Ferreira (2015)
Knowledge Management and Project Management are widely discussed in literature, but the intersection of these themes has been perceived as a promising research area since the knowledge management has the potential to leverage Project Management results. This research focus on knowledge management processes and, in depth, the process of knowledge sharing in order to analyze its relationship with project management processes group considering three perspectives: type of knowledge generated, actors and involved technologies. As main research results, the existing literature is complemented with respect to technologies that support knowledge sharing as well as the involved actors are mapped in each of the project management groups considering their intersections with knowledge sharing. In addition, as knowledge type analysis results was was concluded that it is possible to influence knowledge conversion forms. In addition, it is possible to explore inter-project knowledge sharing opportunities in order to optimize project management results for the organization, there are opportunities to create and store knowledge in an organized manner so it can be retrived when needed, as well as there are ways to stimulate the knowledge sharing. To conclude, it is possible to implement control mechanisms that enable effective knowledge management.